Impact of material surface properties on building performance across a variety of climates - Kokogiannakis, Georgios; Tuohy, Paul; Darkwa, Jo (2012)
Reflective coatings have been promoted for improved energy performance of buildings and are considered in some building regulations such as the California Title 24 standard. This paper provides an analysis of the energy impact of different internal and external surface coatings on heating and cooling energy performance across a variety of climates, constructions and building types. The analysis is undertaken with the ESP-r integrated whole building simulation program. The results are compared with other studies and conclusions are drawn. The effect of these properties is shown to affect the energy performance of buildings and to vary with the context.